Soil Zonation and The Shaking Table Test of The Embankment on Clayey Soil - Ripon Hore; Sudipta Chakraborty; Md. Fayjul Bari; Ayaz Mahmud Shuvon; Mehedi Ahmed Ansary (Department of Geography Education, University of Jember, 2020)
The main objective of this research was to model the zonation of wrap faced embankment on soft clay foundation, by applying a shake table test. Also, to investigate the dynamic behaviors of clay soil, such as acceleration amplification, displacement and pore water pressure of wrap faced embankment. This was done with respect to changes in frequencies of 1 Hz, 3 Hz, 5 Hz, 10 Hz, 12 Hz and 15 Hz respectively. Constant acceleration (0.1 g) and surcharge (19 Kg) were applied by using a laminar box, placed on a shake table testing machine. The main elements of this research were the laboratory test, which was used for preparing reconstitute soil samples, and wrap faced embankment with frequency arrangement. After applying all test parameters, dynamic parameters were increased by rise in elevation with respect to frequency. The result shows that the maximum dynamic parameters were found at the frequency of 10 Hz. It is beneficial to the relative performances of the wrap faced embankment, which is the updated design parameter. Keywords: Seismic; Clay Soil; Frequency; Shake Table Test; Wrap Faced; Soil Zonation Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License